PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP STRUKTUR MODAL (Studi pada Perusahaan Manufaktur yang Terdaftar di PT. Bursa Efek Indonesia Periode 2014-2016) - Saraswati, Niken; Muharam, Harjum (Diponegoro Journal of Management, 2018)
The purpose of this research was to examine the effect of corporate governance structures, represented by the number of commissioners, number of board of directors, institutional ownership, government ownership, and concentration of share ownership on the capital structure of manufacturing companies in Indonesia.        The population in this research are manufacturing companies listed on Indonesia Stock Exchange in 2014-2016 by taking samples based on certain criteria. To test the hypothesis, the research uses multiple regression analysis techniques with a sample of 249 companies.        The results showed that the number of commissioners, the number of directors, and government ownership had no significant effect on the capital structure. Institutional ownership has a positive and significant influence on the capital structure of the capital structure. While the concentration of share ownership has a significant negative effect on the capital structure.